Entry and Competition in a Transition Economy: The Case of Slovakia - Martin Lábaj; Peter Silaniè; Christoph Weiss (University of Economics in Bratislava, Department of Economic Policy, 2013)
The present paper provides first empirical evidence on the effects of entry on market conduct for a transition economy. We estimate size thresholds required to support different numbers of firms for seven retail and professional service industries in a large number of distinct geographic markets in Slovakia. Our results suggest a differential impact of entry on market conduct: while market conduct is unaffected by entry in the north-western parts of Slovakia, competition tends to kick in slowly in most professions in the south-east. This latter region suffers from infrastructure bottlenecks and competitors require a larger increase in the number of customers to come in.
Keywords: L22; D22; M13; R11; 330; entry thresholds; competition; Slovakia; cross section; geographic markets